Lidar observations of aerosol enhancement in the upper troposphere and lower stratosphere. Issue 1 (June 2020) - Ma, Xian; Tu, Houwang; Wang, Yongxian
Abstract: The upper troposphere and the lower stratosphere (UTLS) are the transition areas between the troposphere and stratosphere. Water vapor, cirrus clouds and aerosols in this area have a strong modulation effect on solar short-wave radiation and earth long-wave radiation. Changes in the content and distribution of aerosols in this level will have a radiant forcing impact on the climate. This article uses the observation data of MPL lidar (micropulse lidar) at SACOL station (Semi-arid Climate and Environment Observation Station of Lanzhou University, 34.946°N, 104.93°E) and ERA-Interim reanalysis data from June to December 2011 to study the changes of stratospheric aerosol over SACOL station after Nabro volcano eruption on June 12, 2011. The result indicates that after the Nabro volcanic eruption, there is an aerosol layer with significantly enhanced scattering ratio over the SACOL station, and the depolarization ratio of particles in the aerosol layer is relatively small, mainly spherical particles; by analyzing the backward trajectory of the stronger aerosol layer, it can be determined that the special aerosol layer was caused by the Nabro volcanic eruption.